Drug-Induced Liver Toxicity and Prevention by Herbal Antioxidants: An Overview - Singh, Divya; Cho, William C.; Upadhyay, Ghanshyam (Frontiers in Physiology, 2016)
The liver is the center for drug and xenobiotic metabolism, which is influenced most with medication/xenobiotic-mediated toxic activity. Drug-induced hepatotoxicity is common and its actual frequency is hard to determine due to underreporting, difficulties in detection or diagnosis, and incomplete observation of exposure. The death rate is high, up to about 10% for medication instigated liver danger. Endorsed medications (counting acetaminophen) represented >50% of instances of intense liver failure in a study from the Acute Liver Failure Study Group (ALFSG) of the patients admitted in 17 US healing facilities. Albeit different studies are accessible uncovering the mechanistic aspects of medication prompted hepatotoxicity, we are in the dilemma about the virtual story. The expanding prevalence and effectiveness of Ayurveda and herbal products in the treatment of various disorders led the investigators to look into their potential in countering drug-induced liver toxicity. Several plant products have been reported to date to mitigate the drug-induced toxicity. The dietary nature and less side reactions of the herbs provide them an extra edge over other candidates of supplementary medication. In this paper, we have discussed on the mechanism involved in drug-induced liver toxicity and the potential of herbal antioxidants as supplementary medication.